[I3] Imitation, Iteration and Improvisation: Embodied interaction in making and learning. (November 2015) - El-Zanfaly, Dina
Abstract : I introduce in this paper a new learning and making process that fosters a new ability to make things through the body's direct, iterative engagement with materials, tools, machines and objects. Tested in a variety of educational settings, this method, which I call 'I3' for its three-layer operation of 'Imitation, Iteration and Improvisation', allows learners to develop their sensory experiences to improvise and create on their own. I introduce case studies in order to test I 3 . I challenge the separation of design and construction often reinforced by the use of digital fabrication. I show that learning to make and learning from making emerge together through a situated and embodied interaction among the learner, the materials, the tools and the object in-the-making . Highlights: I challenge the separation of design and construction in making often reinforced by the use of digital fabrication. I introduce a new embodied making and learning process called I 3 . I 3 is comprised of a three-layer operation of Imitation, Iteration and Improvisation . I introduce workshops in different educational settings as case studies to test I 3 . With I 3, learners can improvise and create on their own.